Melt Electrowriting of a Photo‐Crosslinkable Poly(ε‐caprolactone)‐Based Material into Tubular Constructs with Predefined Architecture and Tunable Mechanical Properties. Issue 7 (22nd May 2022) - Pien, Nele; Bartolf‐Kopp, Michael; Parmentier, Laurens; Delaey, Jasper; De Vos, Lobke; Mantovani, Diego; Van Vlierberghe, Sandra; Dubruel, Peter; Jungst, Tomasz
Abstract: Melt electrowriting (MEW) is an additive manufacturing process that produces highly defined constructs with elements in the micrometer range. A specific configuration of MEW enables printing tubular constructs to create small‐diameter tubular structures. The small pool of processable materials poses a bottleneck for wider application in biomedicine. To alleviate this obstacle, an acrylate‐endcapped urethane‐based polymer (AUP), using a poly(ε‐caprolactone) (PCL) (molar mass: 20 000 g mol −1 ) (AUP PCL20k) as backbone material, is synthesized and utilized for MEW. Spectroscopic analysis confirms the successful modification of the PCL backbone with photo‐crosslinkable acrylate endgroups. Printing experiments of AUP PCL20k reveal limited printability but the photo‐crosslinking ability is preserved post‐printing. To improve printability and to tune the mechanical properties of printed constructs, the AUP‐material is blended with commercially available PCL (AUP PCL20k:PCL in ratios 80:20, 60:40, 50:50). Print fidelity improves for 60:40 and 50:50 blends. Blending enables modification of the constructs' mechanical properties to approximate the range of blood vessels for transplantation surgeries. The crosslinking‐ability of the material allows pure AUP to be manipulated post‐printing and illustrates significant differences in mechanical properties of 80:20 blends after crosslinking. An in vitro cell compatibility assay using human umbilical vein endothelial cells also demonstrates the material's non‐cytotoxicity. Abstract : An acrylate‐endcapped urethane‐based polymer (AUP) with a poly( ε ‐caprolactone) (PCL) backbone is tested as novel material for melt electrowriting (MEW). AUP is compatible with MEW and enables postprocessing via UV‐crosslinking. Blending AUP and PCL improves printability and enables tuning mechanical properties of the constructs. The tubular samples are evaluated regarding physicochemical characteristics and reveal mechanical properties comparable to human blood vessels.